DETERMINAN PEMBERIAN MPASI PADA BAYI USIA 6-24 BULAN DI POSYANDU DEWI SARTIKA SURABAYA: DETERMINAN PEMBERIAN MPASI PADA BAYI USIA 6-24 BULAN DI POSYANDU DEWI SARTIKA SURABAYA - Muh Zul Azhri Rustam; Faradila Faizah; AV Sri Suhardiningsih; Sri Anik Rustini (Jurnal Medika Hutama, 2022)
Complimentary food for breast milk (MPASI) is food or drink containing nutrients that is given to infants or children aged 6-24 months and is given gradually according to the baby's age and planning ability to meet nutritional needs, other than breast milk. Objective: The purpose of this study was to analyze the dominant factors in the provision of complementary feeding for infants aged 6-24 months. Methods: The design of this study was a cross-sectional approach. Data analysis using Logistic Regression. The results there is a relationship between knowledge, work, and attitudes with complementary feeding. The dominating factor, in this case, is knowledge because it has a value of 0.006 (ρ<0.05) and affects 18.621 times. Conclusion based on the results of this study knowledge is the dominant factor that has the greatest influence. If the mother's knowledge is good, the better the mother's attitude in providing complementary feeding for infants aged 6-24 months so that complementary feeding is carried out properly. Keywords: Knowledge; Occupation; Attitude; Complementary Foods